Unusual mucoepidermoid carcinoma of the liver misdiagnosed as squamous cell carcinoma by intraoperative histological examination - Guo, Xiao-qin (BioMed Central, 2014)
As rare condition, mucoepidermoid carcinoma may occur in liver although its etiology and pathogenesis is still unclear. We report here a case of intrahepatic mucoepidermoid carcinoma misdiagnosed as cholangiocarcinoma and squamous cell carcinoma by preoperative radiologic and intraoperative histological examinations, respectively. A 60-year-old woman presented with a 1-month history of progressive jaundice, epigastric discomfort, and weight loss with slightly increased carbohydrate antigen 19-9 (CA19-9). Computed tomography (CT) showed a large tumor, 8.0 cm in diameter, in the left lobe of the liver. A preliminary diagnosis of a cholangiocarcinoma of the liver was made. In the intraoperative histological examination, a diagnosis of squamous cell carcinoma was made based on predominantly invasive epidermoid cells with abundant keratinization and absence of mucin-producing cell component. However, postoperative histological diagnosis of the lesion was mucoepidermiod carcinoma of liver by thoroughly microscopical inspection and the presence of mucin-producing cells confirmed by Alcian blue staining. Despite surgical excision and chemotherapy, the tumor showed very aggressive malignancy with tumor recurrence. The patient died shortly afterward, surviving 6 months after surgery. Due to its rarity and distinct morphological features, mucoepidermoid carcinoma might be erroneously interpreted as squamous cell carcinoma by those who were not familiar with this condition in unusual locations. Therefore, removal of sufficient tissue from different portions of the lesion is essential for the surgeons and pathologists to make a precise diagnosis in the intraoperative histological examination. VIRTUAL SLIDE: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/4956311271136060